Kinetics of Olivine Weathering in Seawater: An Experimental Study - Fuhr, Michael; Geilert, Sonja; Schmidt, Mark; Liebetrau, Volker; Vogt, Christoph; Ledwig, Brendan; Wallmann, Klaus (Frontiers in Climate, 2022)
Enhanced weathering of mafic and ultra-mafic minerals has been suggested as a strategy for carbon dioxide removal (CDR) and a contribution to achieve a balance between global CO2 sources and sinks (net zero emission). This study was designed to assess CDR by dissolution of ultramafic sand (UMS) in artificial seawater (ASW). Fine grained UMS with an olivine content of ~75% was reacted in ASW for up to 134 days at 1 bar and 21.5 – 23.9°C. A decline in total alkalinity (TA) was observed over the course of the experiments. This unexpected result indicates that TA removal via precipitation of cation-rich authigenic phases exceeded the production of TA induced by olivine dissolution. The TA decline was accompanied by a decrease in dissolved inorganic carbon and Ca concentrations presumably induced by CaCO3 precipitation. Temporal changes in dissolved Si, Ca, Mg and TA concentrations observed during the experiments were evaluated by a numerical model to identify secondary mineral phases and quantify rates of authigenic phase formation. The modeling indicates that CaCO3, FeOOH and a range of Mg-Si-phases were precipitated during the experiments. Chemical analysis of precipitates and reacted UMS surfaces confirmed that these authigenic phases accumulated in the batch reactors. Nickel released during olivine dissolution, a potential toxic element for certain organisms, was incorporated in the secondary phases and is thus not a suitable proxy for dissolution rates as proposed by earlier studies. The overall reaction stoichiometry derived from lab experiments was applied in a box model simulating atmospheric CO2 uptake in a continental shelf setting induced by olivine addition. The model results indicate that CO2 uptake is reduced by a factor of 5 due to secondary mineral formation and the buffering capacity of seawater. In comparable natural settings, olivine addition may thus be a less efficient CDR method than previously believed.